Leadership Style of Madrasah Principal in Improving Teacher Professionalism at Madrasah Aliyah - Ema Apriana; Andi Warisno; Nur Hidayah (CV. Tripe Konsultan, 2023)
Education for the Indonesian people today is an absolute necessity that must be developed. Education that is managed in an orderly, orderly, and efficient manner can achieve lofty goals, namely creating justice, prosperity, and intelligence for the Indonesian people. The head of the madrasa as an educational leader, judging from the status and method of appointment, is classified as an official leader,